Mentalization-based treatment for adolescents with conduct disorder (MBT-CD): protocol of a feasibility and pilot study - Taubner, Svenja; Hauschild, Sophie; Kasper, Lea A.; Kaess, Michael; Sobanski, Esther; Gablonski, Thorsten-Christian; Schröder-Pfeifer, Paul; Volkert, Jana (Pilot and feasibility studies, 2021)
Conduct disorder (CD) is a complex mental disorder characterized by severe rule-breaking and aggressive behavior. While studies have shown that several therapeutic interventions are effective in treating CD symptoms, researchers call for treatments based on etiological knowledge and potential patho-mechanisms. Mentalization-based treatment (MBT) may represent such a treatment approach: Studies have shown that individuals with CD show mentalizing deficits and that mentalizing might represent a protective factor against the development of the disorder. As MBT focuses on the understanding of social behavior in terms of mental states, fostering mentalizing might help CD individuals to (re)gain an adaptive way of coping with negative emotions especially in social interactions and thus reduce aggressive behavior. For this purpose, MBT was adapted for adolescents with CD (MBT-CD). This is a protocol of a feasibility and pilot study to inform the planning of a prospective RCT. The primary aim is to estimate the feasibility of an RCT based on the acceptability of the intervention and the scientific assessments by CD individuals and their families indicated by quantitative and qualitative data, as well as based on necessary organizational resources to conduct an RCT. The secondary aim is to investigate the course of symptom severity and mentalizing skills.
Gesehen am 09.06.2023